The neural and social correlates of automatic behaviours - Brown, Beverley Jane (2019)
The research in this thesis will focus primarily on the role motor cortex excitability has on social and non-social action behaviours, and in particular behaviours relating to; echophenomena, motor action, contagious behaviours, impulsivity, and action imitation. Inhibition and facilitation, specifically in relation to contagious behaviours, imitation, and impulsivity, will be explored to a greater extent in order to further understanding on how these might be altered in neurodevelopmental conditions. Initial studies chapter 3 to 5 investigated contagious yawning, a form of imitative behaviour related to echophenomena, in typically developed controls (TDC). Echophenomena is related to early social cognition and is altered in some neurodevelopmental conditions such as Autism spectrum disorders and Gilles de la Tourette’s syndrome. The first study was a within subjects’ design that utilised both physiological (TMS) measures of cortical activity alongside behavioural measures of contagious yawning. Subsequent studies were both within and between subjects’ designs and sought to modulate motor cortex excitability during both automatic social and non-social behaviours. These same neurophysiological techniques were then used to explore the relationship between corticospinal excitability and impulsive behaviours. Measures of impulsivity were assessed using modified ‘traffic light’ behavioural paradigms.